2009
DOI: 10.1016/j.brainres.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar defects in a mouse model of juvenile neuronal ceroid lipofuscinosis

Abstract: Juvenile neuronal ceroid lipofuscinosis (JNCL), or Batten disease, is a neurodegenerative disease resulting from a mutation in CLN3, which presents clinically with visual deterioration, seizures, motor impairments, cognitive decline, hallucinations, loss of circadian rhythm, and premature death in the late-twenties to early-thirties. Using a Cln3 null (Cln3−/−) mouse, we report here several deficits in the cerebellum in the absence of Cln3, including cell loss and early onset motor deficits. Surprisingly, earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 55 publications
1
78
0
Order By: Relevance
“…Over the last decade, we have been characterizing each of the available mouse models of NCL, documenting the onset and progression of pathological changes [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and testing the efficacy of a range of therapeutic interventions [35][36][37][38]. Our studies have revealed a number of new and surprising pathological features that are broadly shared by the different forms of NCL, but with subtype-specific differences in the staging of these events and some more pronounced differences between certain forms of NCL.…”
Section: What Do We Know About Ncl Pathogenesis So Far?mentioning
confidence: 91%
See 1 more Smart Citation
“…Over the last decade, we have been characterizing each of the available mouse models of NCL, documenting the onset and progression of pathological changes [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and testing the efficacy of a range of therapeutic interventions [35][36][37][38]. Our studies have revealed a number of new and surprising pathological features that are broadly shared by the different forms of NCL, but with subtype-specific differences in the staging of these events and some more pronounced differences between certain forms of NCL.…”
Section: What Do We Know About Ncl Pathogenesis So Far?mentioning
confidence: 91%
“…Neuron loss in all forms of NCL is invariably preceded by localized glial activation of one type or another [24,25,27,30,31,33,39], and this process starts much earlier than previously suspected, already being evident prenatally in sheep models of NCL [43]. There is also evidence for a direct relationship between the extent of astrocytosis, microglial activation and neuron loss in human NCL post-mortem material [15,32,37]. We have begun exploring this relationship in more detail and have obtained preliminary evidence that the biology of astrocytes and microglia may be compromised in certain forms of NCL.…”
Section: Pathways To Neuron Loss?mentioning
confidence: 97%
“…Thus, some GSLs, e.g., ceramide, GlcCer, and LacCer, or LacSph, may cause Purkinje cell loss, but others may not. Several mouse models unrelated to GSL disorders also present with Purkinje cell loss (263)(264)(265), thereby implicating other pathways in degeneration of these cells. The mechanism(s) by which Purkinje cells degenerate are unknown, but negative TUNEL assays in Sap C Ϫ / Ϫ and Sap D Ϫ / Ϫ mouse brains suggest that apoptosis is not the major mechanism ( 243,266 ).…”
Section: Neuronal Degenerationmentioning
confidence: 99%
“…This increased surface expression of AMPA receptors is obviously not neurotoxic, since neurodegeneration in Cln3 −/− mice is first detected at the age of 6 months. The elevated surface level of AMPA receptors, however, is certainly able to dysregulate normal glutamatergic neurotransmission, resulting in the pronounced early motor coordination deficit of Cln3 −/− mice [40]. This notion is supported by our previous results demonstrating that attenuation of AMPA receptor activity in 1-month old Cln3 −/− mice by a single intraperitoneal injection of a specific AMPA antagonist immediately improves their motor coordination [20].…”
Section: Discussionmentioning
confidence: 73%
“…Cln3 −/− mice, similarly to patients with juvenile CLN3 disease, show an early deficit in motor coordination as measured by the rotarod test [22, 40]. Exploring the possible cause(s) of the motor incoordination in Cln3 −/− mice we have previously found that Cln3 −/− cerebellar granule cells in dissociated cultures and in organotypic cerebellar slice cultures are significantly more sensitive to AMPA, but not NMDA, receptor-mediated toxicity than their wild type counterparts [22], indicating an abnormally enhanced AMPA receptor function.…”
Section: Introductionmentioning
confidence: 99%